Parametric model and poverty (Pa) measures - Joshi, P.D. (2006)
The design effect and efficiency of sample design in estimating frequency distribution needs to be looked into. Further, spatial and inter temporal changes in dimensions of poverty may not depict the real situation for want of error estimates since poverty measures are estimated on the basis of sample surveys which are subject to sampling variance. - Reproduced.
Keywords: Poverty